Developmental Trends in Different Types of Spontaneous False Memories: Implications for the Legal Field. (9th July 2013) - Otgaar, Henry; Howe, Mark L.; Peters, Maarten; Sauerland, Melanie; Raymaekers, Linsey; Otgaar, Henry; Sauerland, Melanie; Petrila, John P.
<x xml:space="preserve">Abstract</x> In an emerging area of memory research, it is becoming apparent that one particular type of false memory, called spontaneous false memory, follows a developmental trajectory that is the opposite of what is commonly assumed in false memory research – that is, spontaneous false memories are more likely to occur in adults than in children. The present study focused on developmental trends of different types of spontaneous false memories. Specifically, in the current study, 6–8 year‐olds, 10–12 year‐olds, and adults were presented with two methods to induce spontaneous false memories: (i) semantically related word lists that are commonly used to evoke spontaneous false memories [i.e, Deese–Roediger–McDermott (DRM) paradigm]; and (ii) a video in which related details were not shown but were presented during a recognition task. The results showed that children were more likely to form false memories than adults in the video false memory paradigm, whereas DRM false memories were more evident in adults than in children. Furthermore, we found that on a general level, DRM false memories were positively related to video spontaneous false memories. We explain that stimuli that contain obvious themes attenuate or even reverse developmental trends in spontaneous false memories. Copyright © 2013 John Wiley & Sons, Ltd.